2022
DOI: 10.1017/s0022278x21000422
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Ebola at bay: public authority and ceremonial competence in rural Sierra Leone

Abstract: Ebola Virus Disease struck Sierra Leone in May 2014. An international response was instrumental in ending the epidemic by December 2015 and has been extensively documented. Less attention has been paid to local responses. Here, we focus on a case in which there was no infection despite high infection in neighbouring areas. This brings into focus the role of customary public authority in implementing successful controls. We pay particular attention to the activities of a chiefdom Ebola Task force committee chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Local administrations also competed to turn their chiefdom from 'red' (active cases) to 'green' (no cases), even if, given the political salience of 'red' and 'green' as the colours associated with the two main rival political parties in Sierra Leone, the choice of colour coding might have been queried as somewhat unfortunate. Kamara et al (2022) describe the strength of protest when one chiefdom Ebola task force committee found it had wrongly been credited with a 'positive' case (a local resident who had been infected, and recovered, elsewhere). The Paramount Chief took considerable trouble to have this anomaly reclassified (exactly as Douglas, 1986 predicts).…”
Section: Comparing Ebola and Covid-19 Institutionallymentioning
confidence: 99%
See 1 more Smart Citation
“…Local administrations also competed to turn their chiefdom from 'red' (active cases) to 'green' (no cases), even if, given the political salience of 'red' and 'green' as the colours associated with the two main rival political parties in Sierra Leone, the choice of colour coding might have been queried as somewhat unfortunate. Kamara et al (2022) describe the strength of protest when one chiefdom Ebola task force committee found it had wrongly been credited with a 'positive' case (a local resident who had been infected, and recovered, elsewhere). The Paramount Chief took considerable trouble to have this anomaly reclassified (exactly as Douglas, 1986 predicts).…”
Section: Comparing Ebola and Covid-19 Institutionallymentioning
confidence: 99%
“…The Paramount Chief took considerable trouble to have this anomaly reclassified (exactly as Douglas, 1986 predicts). The minutes of the chiefdom Ebola task force committee record that if the anomaly could not be removed administratively, then the person should be obliged to remove themselves physically (Kamara et al, 2022)! In all, people concluded that the way to beat Ebola was to follow the law.…”
Section: Comparing Ebola and Covid-19 Institutionallymentioning
confidence: 99%